4CPS-014 Follow-up to recommendations about renal function monitoring in elderly patients treated with sodium-glucose co-transporter 2 inhibitors - Gracia, P (Eur J Hosp Pharm, 2018)
BACKGROUND: The efficacy of sodium-glucose co-transporter 2 inhibitors (iSGLT) decrease with decreasing glomerular filtration rate. The summary of products’ characteristics recommends restriction in the use of iSGLT to patients with creatinine clearance (CrCl) >60 ml/min/1.73 m(2) and treatment should be suspended if CrCl <45 ml/min/1,73 m(2). PURPOSE: To describe the adherence to guidelines’ recommendations about renal function monitoring in patients aged over 75 years treated with iSGLT. MATERIAL AND METHODS: Transversal, descriptive study in patients aged over 75 years from six primary healthcare centres of the same referral hospital, under treatment with iSGLT-2 as of 30 September 2017. Data were obtained from electronic health records of primary care and referral hospitals. RESULTS: Fifty-nine patients were included: 55.17% male, mean age 79 (SD 2.6) years and mean CrCl (CKD-EPI) 66.1±13.3 mL/min/1.73 m(2). Seventeen patients were lost to follow-up, 12 finished treatment before 30 September 30th 2017 and five due to lack of analytical data. All patients were diagnosed with type-2 diabetes mellitus, 59.32% obese (IMC >30). At the beginning of treatment 62.7% IC 95% (49.1%–75%) had CrCl >60 mL/min/1.73 m(2). 89.5%, 95% CI: 79.2% to 96. 2% patients followed renal function monitoring recommendations. Six patients had not correct monitoring, three patients did not have any follow-up and 3 patients had ClCr <45 mL/min/1.73 m(2) and continued treatment. CONCLUSION: Patients treated with iSGLT-2 have a good control of renal function Most of them followed renal function monitoring recommendations. There were patients whose renal function did not align to the recommendations at the beginning of treatment. REFERENCES AND/OR ACKNOWLEDGEMENTS: 1. Summary of products. http://www.ema.europa.eu/ema/ 2. Update of hyperglycaemia algorithm. http://www.redgdps.org/redgdpsresponde/madrid.php No conflict of interest